Systemic lupus erythematosus-a good maternal and fetal outcome - Lewis, Preeti; Pal, Ashrulina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Systemic lupus erythematosus (SLE) is a multisystemic autoimmune disease which primarily affects women in their reproductive years. The fertility is generally unaffected except in women with active disease, significant impairment of renal function, or high dose corticosteroid or cyclophosphamide therapy, which can result in ovarian dysfunction. This case report elaborates on the course of the pregnancy and the favourable maternal and fetal obstetric outcome of a 28-year-old female with known case of hypothyroidism who presented with chief complaints of generalised swelling all over the body and exertional dyspnoea and was later diagnosed to be a case of focal proliferative lupus nephritis, class III (ISN/RPS) on renal biopsy done postpartum. The effect of pregnancy on maternal disease is controversial. While some studies report exacerbation of SLE during pregnancy,others have not reported increased flares. The only study on this aspect of SLE from our country did not report a flare-up of disease during pregnancy.